Management of Hand Burns - Fatih Irmak; Selami Serhat Şirvan; Sevgi Kurt Yazar; Kamuran Zeynep Sevim; Semra Hacıkerim Karşıdağ (Turkish Journal of Plastic Surgery, 2017)
Objective: The hand is one of the most frequently affected body parts by burn injuries with a rate of 80% among all burn wounds. Early and effective treatment ensures the best chance of survival as well as a good functional prognosis. The aim of this study was to determine the epidemiology, variation, relationship between etiology and hospital stay, clinical features, and management of hand burns. Material and Methods: This retrospective study was conducted the University of Health Sciences; Şişli Hamidiye Etfal Application and Research Center, Departmant of Plastic, Reconstructive and Aesthetic Surgery and the Intensive Burn Care Unit between April 2009 and April 2014. Burns were assessed based on etiology, anatomical location, percentage of total body surface area affected, and depth of injury. Treatment was categorized as conservative, elective operative, or urgent operative. Results: In the study period, 788 patients were admitted to our Burn Unit. Of these, 240 were females (30.5%) and 548 were males (69.5%). The most common type of burn injury in this study was thermal injury (695 cases; 88.2%), followed by electrical injury (67 cases; 8.5%), and chemical, frictional or unknown injuries (26 cases; 3.3%). Majority (more than 85%) of the patients had second-degree burns, and some had third-degree burns. Conclusions: Burns commonly affect the hands, and many functional problems may develop if appropriate basic treatments are neglected. The best treatment for burns is prevention. Appropriate indoor arrangement and simple but effective measures that can be taken at home can significantly reduce burn trauma exposure.